{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

Chapter_12

Chapter_12 - CHAPTER 12 12.1 2 2 2 1 J fb m = E f m-1 n E b...

This preview shows pages 1–6. Sign up to view the full content.

244 CHAPTER 12 12.1 Differentiating with respect to a complex variable: 12.2 (a) Suppose we write Then substituting these relations into Burg’s formula: , J fb m , 1 2 -- E f m -1 n ( ) 2 [ ] E b m -1 n -1 ( ) 2 [ ] + ( ) 1 κ m 2 + ( ) = κ m E f m -1 n ( ) b m -1 * n -1 ( ) [ ] κ m * E b m -1 n -1 ( ) f m -1 * n ( ) [ ] + + J fb m , ∂κ m ----------------- κ m E f m -1 n ( ) 2 [ ] E b m -1 n -1 ( ) 2 [ ] + ( ) = E b m -1 n -1 ( ) f m -1 * n ( ) [ ] E b m -1 n -1 ( ) f m -1 * n ( ) [ ] + + κ m E f m -1 n ( ) 2 [ ] E b m -1 n -1 ( ) 2 [ ] + ( ) = 2 E b m -1 n -1 ( ) f m -1 * n ( ) [ ] + f m i ( ) f m -1 i ( ) κ ˆ m n ( ) b m -1 i -1 ( ) + = b m i ( ) b m -1 i ( ) κ ˆ m n ( ) f m -1 i ( ) + = κ ˆ m n ( ) 2 b m -1 i -1 ( ) f m -1 * i ( ) i =1 n f m -1 i ( ) 2 b m -1 i -1 ( ) 2 + i =1 n ------------------------------------------------------------------ = 2 b m -1 i -1 ( ) f m -1 * i ( ) 2 b m -1 n -1 ( ) f m -1 * n ( ) + i =1 n E m -1 n -1 ( ) f m -1 n ( ) 2 b m -1 n -1 ( ) 2 + + ----------------------------------------------------------------------------------------------------------- =

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
245 Cross-multiplying and proceeding in a manner similar to that described after Eqs. (12.12) and (12.13) in the text, we finally get (b) The algorithm so formulated is impractical because to compute the updated forward prediction error f m ( n ) and backward prediction error b m ( n ) we need to know the updated . This is not possible to do because the correction term for requires knowledge of f m ( n ) and b m ( n ). 12.3 For the transversal filter of Fig. 12.6 in the text we have: tap-weight vector = k M ( n ) tap-input vector = u M ( i ), i = 1,2,..., n desired response, d ( i ) = The a posteriori estimation error equals The deterministic cross-correlation vector equals We also note that Hence, the sum of weighted error squares equals κ ˆ m n ( ) κ ˆ m n -1 ( ) f m -1 * n ( ) b m n ( ) b m -1 n -1 ( ) f m * n ( ) + E m -1 n -1 ( ) --------------------------------------------------------------------------------- = κ ˆ m n ( ) κ ˆ m n ( ) 1 i n = 0 i n -1, 1 , = e i ( ) d i ( ) k M H n ( ) u M i ( ), i 1 2 n , , , = = φ n ( ) φ n ( ) λ n -i u M d * i ( ) i =1 n = u M n ( ) = E d n ( ) λ n - i d i ( ) 2 i =1 n 1 = =
246 We note that the inner product is a real-valued scalar. Hence, 12.4 We start with where is the tap-input vector, is the past value of the deterministic correlation matrix, and is its present value. Hence, where I is the identity matrix. Hence, taking the determinants of both sides: (1) But, We may therefore rewrite Eq. (1) as E min n ( ) E d n ( ) φ H n ( ) w ˆ n ( ) = 1 u M H n ( ) k m n ( ) = u M H n ( ) k m n ( ) E min n ( ) 1 k m H n ( ) u m n ( ) = γ M n ( ) = Φ m n ( ) λΦ m n -1 ( ) u m n ( ) u m H n ( ) + = u M n ( ) Φ m n -1 ( ) Φ m n ( ) λΦ m n -1 ( ) Φ m n ( ) u m n ( ) u m H n ( ) = Φ m n ( ) I u m n ( ) u m H n ( )Φ m 1 n ( ) [ ] = λ det Φ m n -1 ( ) [ ] det Φ m n ( ) [ ] det I u m n ( ) u m H n ( )Φ m 1 n ( ) [ ] = det I u m n ( ) u m H n ( )Φ m 1 n ( ) [ ] det I u m H n ( )Φ m 1 n ( ) u m n ( ) = 1 u m H n ( )Φ m 1 n ( ) u m n ( ) = γ m n ( ) =

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
247 Hence, we may express the conversion factor as 12.5 (a) The ( m +1)-by-( m +1) correlation matrix may be expressed in the form (1) Define the inverse of this matrix as (2) Hence, from Eqs. (1) and (2): From this relation we deduce the following four equations: (3) (4) λ det Φ m n -1 ( ) [ ] det Φ m n ( ) [ m n ( ) = γ m n ( ) γ m n ( ) λ det Φ m n -1 ( ) [ ] det Φ m n ( ) [ ] ---------------------------------- = Φ m +1 Φ m +1 n ( ) U n ( ) φ 1 H n ( ) φ 1 n ( ) Φ m n -1 ( ) = Φ m +1 1 n ( ) α 1 β 1 H β 1 Γ 1 = I m +1 Φ m +1 n ( )Φ m +1 1 n ( ) = U n ( ) φ 1 H n ( ) φ 1 n ( ) Φ m n -1 ( ) α 1 β 1 H β 1 Γ 1 = U n ( )α 1 φ 1 H n ( )β 1 + U n ( )β 1 H φ 1 H n ( )Γ 1 + φ 1 n ( )α 1 Φ m n -1 ( 1 + φ 1 n ( )β 1 H n ( ) Φ m n -1 ( 1 + = U n ( )α 1 φ 1 H n ( )β 1 + 1 = U n ( )β 1 H φ 1 H n ( )Γ 1 + 0 =
248 (5) (6) Eliminate β 1 between Eqs. (3) and (5): Hence, (7) which is real-valued. Correspondingly, (8) From Eq. (6): (9) Check: Substitute Eqs. (8) and (9) into the left hand side of Eq. (4):

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}

What students are saying

• As a current student on this bumpy collegiate pathway, I stumbled upon Course Hero, where I can find study resources for nearly all my courses, get online help from tutors 24/7, and even share my old projects, papers, and lecture notes with other students.

Kiran Temple University Fox School of Business ‘17, Course Hero Intern

• I cannot even describe how much Course Hero helped me this summer. It’s truly become something I can always rely on and help me. In the end, I was not only able to survive summer classes, but I was able to thrive thanks to Course Hero.

Dana University of Pennsylvania ‘17, Course Hero Intern

• The ability to access any university’s resources through Course Hero proved invaluable in my case. I was behind on Tulane coursework and actually used UCLA’s materials to help me move forward and get everything together on time.

Jill Tulane University ‘16, Course Hero Intern